2006
DOI: 10.1080/08035250600667383
|View full text |Cite
|
Sign up to set email alerts
|

Sensory and affective components of pain as recorded with the Pain‐O‐Meter (POM) among children with acute and chronic pain

Abstract: Further studies will be required to determine the suitability of using the POM-WDS with children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The Swedish version of the instrument has proven useful in children aged 6 to 16 years who suffer from acute and chronic pain. 25 The Painometer measures pain intensity, quality, location, and duration at the time of testing and has demonstrated good reliability and validity. 25,26 …”
Section: Painometer (Dola Health Systems Baltimore)mentioning
confidence: 99%
“…The Swedish version of the instrument has proven useful in children aged 6 to 16 years who suffer from acute and chronic pain. 25 The Painometer measures pain intensity, quality, location, and duration at the time of testing and has demonstrated good reliability and validity. 25,26 …”
Section: Painometer (Dola Health Systems Baltimore)mentioning
confidence: 99%
“…Van Laerhoven et al [ 12 ] found a 5-point VRS to be preferred over VAS or NRS in children 6 to 18 years of age, but all scale types showed comparable reliability. In contrast, Jylli et al [ 13 ] found that younger children (ages 6 to 11 years) in their sample (overall range between 6 and 16 years of age) did not fully understand all descriptive words in a 5-point VRS, and that the VRS was not highly correlated with a pain VAS. Bailey et al [ 14 ] found the VAS, NRS, and VRS to be reliable and valid in evaluating pain in children 8 to 17 years of age, but the scores produced were not interchangeable.…”
Section: Resultsmentioning
confidence: 82%
“…The VRS scale, the VAS and the NRS were of comparable reliability. Jylli et al 2006 [ 13 ], Direct, C Cross-Sectional Study; Children aged 6 to 16 years old VAS; VRS Children 6 to 11 years knew fewer words than children 12 to 16 years to describe pain. Further studies are needed to determine the suitability of using 5-point VRS with word descriptors of pain with children of all ages.…”
Section: Resultsmentioning
confidence: 99%